Pengaruh pasar tunggal Eropah (single European market) terhadap perdagangan antara Indonesia dan Poland - Teguh Santoso, Hadi Wibowo (2012)
This study was conducted based on the fenomena of world orientation changes from political conflict to economic competition marked by the emergence of regional economic blocks. There are four main issues that this study was based, which are European Union’s interest on Single European Market, the relationship between Single European Market and Poland, the improvement of Indonesia-Poland trade after the establishment of the Single European Market, and whether the Single European Market influenced Indonesia-Poland trade. The objectives of this study were to examine, understand and explore the Single European Market as a regional market in tandem with the position of Indonesia-Poland trade after its establishment, and its influence on Indonesia-Poland trade. This study also explored the practical aspects concerning the implementation of Indonesia strategic plan towards the establishment of the Single European Market. The method used was descriptive method. Data were collected through secondary resources, which were analyzed by the use of Linier Regression. The determination between variables was examined by the use of Coefficient of Determination, while the significance between variables was utilized by the use of Significance-t. This study found out that the Single European Market strongly determines the trade between Indonesia-Poland. This study had established and concluded that Single European Market significantly influences Indonesia-Poland trade. The result of this study could become a platform for future studies related to Indonesia foreign trade with European countries to support Indonesian government in formulating a more effective strategic plan. To be specific, the result of this study could become a reference for Indonesian government in formulating its foreign trade policy, especially in its trade with Poland.